The MSR-MSRA MT System for NIST Open Machine Translation 2008 Evaluation - He, Xiaodong; Gao, Jianfeng; Quirk, Chris; Nguyen, Patrick; Menezes, Arul; Moore, Robert; Toutanova, Kristina; Yang, Mei; Dolan, Bill; Li, Mu; Li, Chi-Ho; Zhang, Dongdong; et al. (The 2008 NIST Open Machine Translation Evaluation Workshop, 2008)
A system combination framework is used for this entry. Within this framework, up to six individual systems are combined to produce the final MT output.